2017
DOI: 10.1002/cctc.201700492
|View full text |Cite
|
Sign up to set email alerts
|

A Facile One‐Step Synthesis of Fe‐Doped g‐C3N4 Nanosheets and Their Improved Visible‐Light Photocatalytic Performance

Abstract: A simple one‐step pyrolysis process (compared with the routine method of liquid exfoliation and impregnation) was designed to synthesize Fe‐doped graphitic carbon nitride (g‐C3N4) nanosheets with NH4Cl as dynamic gas template and FeCl3 as the Fe source. Results of XPS and DRS indicated that the Fe species might exist at the state of Fe3+ and form Fe−N bonds with N atoms, thereby expanding visible light absorption regions and reducing the band gap of g‐C3N4 nanosheets. Doping certain amounts of Fe could promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(157 citation statements)
references
References 52 publications
7
148
1
1
Order By: Relevance
“…Intercalation and the presence of amorphous Ni + x in the GNi photocatalyst further enlarged the specific surface area and increased the active sites and boosted the light harvesting capability. An exfoliated nanosheet morphology also supports the in‐plane transport of electrons and holes . The C−N heterocycle bonds with O and the Ni acts as a charge transport bridge, thus separating the electron and holes in the g‐C 3 N 4 nanosheets through a C−O−Ni bridge.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Intercalation and the presence of amorphous Ni + x in the GNi photocatalyst further enlarged the specific surface area and increased the active sites and boosted the light harvesting capability. An exfoliated nanosheet morphology also supports the in‐plane transport of electrons and holes . The C−N heterocycle bonds with O and the Ni acts as a charge transport bridge, thus separating the electron and holes in the g‐C 3 N 4 nanosheets through a C−O−Ni bridge.…”
Section: Resultssupporting
confidence: 66%
“…The XPS survey spectrum of the GNi4 sample displayed peaks of C 1s, N 1s, Ni 2p and O 1s (Figure S3). In the survey spectra, no peaks corresponding to Cl from the precursor NH 4 Cl were observed, confirming its role only as a dynamic gas template to increase the surface area . The C 1s spectra of the GNi4 photocatalyst is shown in Figure a.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Few g‐C 3 N 4 composites have also been developed. For example, Fe‐g‐C 3 N 4 has been developed for degradation of methylene blue, water splitting, photo‐oxidation of benzene to phenol and decomposition of nitric oxide . BiVO 4 ‐g‐C 3 N 4 nanocomposites was used for oxidation of alcohol/amines, VO‐g‐C 3 N 4 was employed for the oxidative esterification of alcohols, graphene/C 3 N 4 composites have used for visible‐light photocatalytic H 2 ‐production, g‐C 3 N 4 / N ‐doped graphene/NiFe‐layered double hydroxide used for solar‐driven photoelectrochemical water oxidation, Pd‐g‐C 3 N 4 was developed for Sonogashira reactions .…”
Section: Figurementioning
confidence: 99%
“…For a high‐efficiency photocatalyst, efficient light harvesting is an important issue. It has been demonstrated that for wide‐gap semiconductors, the absorption edge can be extended to the visible‐light region by coupling with 2D materials, such as monolayer MoS 2 and graphene . To reveal the influence of monolayer or few‐layer SnS on the optical properties of MAPbI 3 , the UV/Vis absorption spectra of monolayer SnS, the pure MAPbI 3 (100) surface, and the SnS/MAPbI 3 (100) heterostructures were calculated over the electronic structure obtained with the local density approximation (LDA), including the vdW interactions.…”
Section: Resultsmentioning
confidence: 99%